Peningkatan Aktivitas dan Hasil Belajar Siswa Melalui Blog Berbasis QR-Code dan Edu-Fun Book - Nurwijaya, Sigid (Jurnal Didaktika Pendidikan Dasar, 2023)
Based on its objectives, the learning of 2013 curriculum is oriented towards increasing and balancing among attitudes, skills and knowledge. From the results of observations at Public Elementary School Ngraket, the process of learning has not been able to maximize student activities. Student learning outcomes have not been able to reach the specified KKM. Based on this situation, learning improvements were made through the using of QR-Code-Based Blog media assisted by Edu-Fun Book. In addition, through the QR-Code-Based Blog media, students are introduced to new learning methods, which refer to 21st century skills (digital literacy). It has proven to be effective and successful, in terms of the process assessment and final assessment. QR-Code-Based Blog Media assisted by Edu-Fun Book was able to increase student learning activities with an average score of 4.5 on a scale of 1-5. Student learning outcomes also have significant increase. 19 students out of 20 students (95%) managed to reach the minimum standard of scoring (KKM) with an average score of 85. It means that there is an increase of 14 points from the previous learning that did not use QR-Code-Based Blog media assisted by Edu-Fun Books. Based on these data, it can be concluded that the QR-Code-Based Blog media assisted by Edu-Fun Book has succeeded in increasing student activity and learning outcomes.